The Use of Critical Pedagogy Principles in Teaching English as a Foreign Language (EFL) for Senior High School Students in Subang - Slamet Wahyudi Yulianto Yulianto (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2020)
Three research questions are addressed are: (1) How can CP principles be used in teaching EFL for senior high school students? (2) What learning materials are suitable to be used in using CP principles to teach EFL for senior high school students? (3) What are benefits and challenges of using CP principles in teaching EFL for senior high school students? In uncovering the answers for those questions, several data collection techniques are employed, namely questionnaire, classroom observation, interview, and learning as well as teaching journals. The collected data, after being triangulated, were then analyzed by transcribing, categorizing, coding, and interpreting. It is revealed that there are 23 activities can be performed when using CP principles in teaching EFL for senior high school students. It is also uncovered that there are four conditions should be fulfilled by the learning material before it can be used in CP-principles-informed EFL classrooms for senior high school students. Additionally, there are three categories of challenges are (1) students’ limited English proficiency, (2) cultural problems, and (3) pre-determined curriculum. In the meantime, the four types of benefits are (1) new experience, (2) new knowledge acquisition, (3) increased language awareness, and (4) improved English proficiency.